Fabrication and Performance Analysis of Single-Mode Polymer Waveguides and Devices - Han Wu; Ruizhi Jia; Fuling Wang; Liuge Du; Xiao Xu; Jia Zhao (IEEE Photonics Journal)
Low-cost lithography and wet development process are optimized for fabricating single-mode polymer waveguides and de-vices with small gap structures on FR4 substrate. The fabricated single-mode waveguide with core dimension of 6.04 μm × 6.05 μm exhibits the transmission loss of 1.47 dB/cm and the double-end coupling loss of 1.58 dB with single-mode fibers at 1310 nm. The relationship between the bending loss and the bending radius is also investigated, and a bending radius of larger than 20 mm is recommended. In order to verify the reliability of the optimized process in fabricating devices with small feature sizes, power splitters based on directional coupler and multimode interference are designed and fabricated, and the measurement results show good agreement with the simulation results.